Momentum Trading Strategies in the UK Commodity Futures Market - Mistry, Krishna (2010)
Whilst the majority of evidence supports the superiority of the momentum technique in the stock market, this article tests the presence of short to medium term price continuation in the UK commodity futures market. The paper assesses the effectiveness of the momentum strategy using agricultural commodity futures contracts that are traded on the London International Financial Futures and Options Exchange (LIFFE) and the Baltic Futures Exchange (BFE) from 1990 to 2010. Furthermore, the paper aims to ascertain the underlying rationale that drive the momentum effect, providing a credible explanation where two central risk based explanations are assessed. Firstly static macroeconomic variables are considered using a simple unconditional multifactor model based on the equity, bond and commodity markets. Secondly, the time varying risks associated with these explanatory variables are considered through the addition of a market proxy that captures the time variation of all three indices. While the article identifies the significant performance of all 30 momentum strategies tested, the results indicate that the abnormal returns of momentum strategy are not limited to horizon periods ranging between 3 and 12 months, as the finance literature documents. Furthermore, the results show that the superior performance of the momentum strategy can be considered, to a certain degree, a compensation for the static and time varying risk factors analysed.